HARMONISASI MASYARAKAT MUSLIM DAN KRISTEN: POLA INTERAKSI BERMASYARAKAT DUKUH PURBO - Muhammad Khoiruzzadi; Lia Dwi Tresnani (Harmoni, 2022)
Purbo Hamlet is one of the hamlets in Jolotigo Village, Pekalongan Regency, the majority of which are Protestant Christians, and the rest are Muslims. In their social life, the people of Dukuh Purbo, both Muslims and Christians, both establish harmonious relationships and prioritize living together with one another. The attitude of tolerance and dialogue between the two communities for religion in Dukuh Purbo is an urgent matter and should not be negotiable in Hamlet Purbo. This study aims to explain cooperative relationships that can form harmonious relationships that have been passed down from generation to generation in Dukuh Purbo, factors that can build harmonization relationships in Hamlet Purbo, and patterns of interaction carried out by inter-religious communities in Hamlet Purbo. This research includes field research using a qualitative approach. The selection of research subjects using purposive sampling technique. The primary subjects in this study were the hamlet head of Dukuh Purbo, Islamic religious leaders and Christian religious leaders, and four community members who were active in community activities in Dukuh Purbo. Methods of data collection is done by interview, observation, and documentation. Data analysis was carried out by data reduction, data presentation, and drawing conclusions. The results of the study explain that there are three forms of harmonization between religious communities in Dukuh Purbo, namely harmonization in social society, harmonization in formal education, and harmonization in sacred religious moments. To maintain and strengthen harmonization, firstly, tolerance and mutual respect are instilled as early as possible from the family, school, and community environment, and a sense of belonging to each other, and secondly, two-way interactions carried out by community leaders, religious leaders, and the general public Dukuh Purbo.